The divided heart : essays on Protestantism and the Enlightenment in America - May, Henry F. (Henry Farnham), 1915-2012 (Oxford University Press, 1991)
Bringing together essays by a leading intellectual and religious historian, The Divided Heart is a collection of recent reflections, sometimes with a considerable autobiographical element, by Henry F. May on the conflict between Protestantism and the Enlightenment that runs throughout the history of American culture. Summarizing May's opinions on recent historiographical arguments, the introduction to The Divided Heart tells of his own development as a historian, major influences upon his thinking, and how his practicing assumptions grew. Covering religion, there are essays on early American h.